(untitled) (Revista de Administração, 2013)
This paper presents the results of a quantitative, exploratory and descriptive research, which analyzed 4,544 papers published in five annals of EnANPAD (Encontro da Associação Nacional de Pós-Graduação e Pesquisa em Administração), involving the concept of methodological triangulation. Considering the potential benefits of triangulation for the research in Social Sciences, specifically for Administration, in contrast to the difficulties that still exist for conducting researches of this nature, as well as the existence of resistance to this method, this paper aimed to demonstrate the incidence of studies that used triangulation as a methodological option among the articles that were published in the annals of EnANPAD in the period of 2007-2011 and, as the main goal, to analyze the methodological profile of these articles. It is hoped that this profile indicates the way that triangulation has been worked in Administration research field, as well as possible ways to overcome difficulties related to conducting research that requires the combination of methods of different nature. As main results, were the low incidence of the use of triangulation, the significant formation of partnerships among researchers to conduct the studies with triangulation, and the significant combination of traditional methods of collecting and analyzing data.